NEONATAL CANDIDA INFECTIONS AND THE ANTIFUNGAL SUSCEPTIBILITIES OF THE RELATED CANDIDA SPECIES - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2010)
Among nosocomial infections in the newborns, the incidence of fungal infections has been rising over the last decades. Fluconazole has been a new option for treatment however, expanded use of the drug brought up the development of resistance. In this study, species of the Candida isolates from neonates with candida infections, their antifungal susceptibilities and the effectiveness of the therapy were evaluated. All the species of Candida isolates from blood, urine and sterile body fluids of 54 neonates and their antifungal susceptibilities were evaluated retrospectively over the 13-year period. Demographic characteristics, risk factors, infection foci, Candida species causing infection and their in vitro susceptibilities for fluconazole (FCZ) and amphotericin B (AMB) and treatment responses were analyzed. The antifungal susceptibility testing of isolates was performed by microdilution technique. The median birth weight and gestational age of the study groups were 1 735 (660-3990) g and 33 (24-40) weeks, respectively. Among the patients, 19 (35%) were term, while 35 (65%) were preterm [< 32 weeks n= 20 (37%), < 28 weeks n= 7 (13%)]. The percentage of low birth weight infants was 65% (42% was < 1500 g, 13% was < 1000 g). Candida spp. were isolated mostly from blood samples (63%), followed by urine (46%), cerebrospinal fluid (CSF; 5%), peritoneal fluid (3%) and endotracheal aspirate (2%). Multifocal growth was determined in 10 (18%) cases. The isolated species were C.albicans (n= 36) as being the most common isolate followed by C.parapsilosis (n= 12), C.tropicalis (n= 1), C.kefyr (n= 1), C.lusitaniae (n= 1), C.pelluculosa (n= 1) and Candida spp. (n= 2). Prior antibiotic use, long term hospitalization, total parenteral nutrition and use of lipid solutions, prematurity and catheter use were determined as the most frequently associated factors causing candidal infections. A congenital abnormality, mainly myeloschisis and hydrocephaly, was detected in 18 (33%) of the cases. Overall FCZ resistance rate was 5.5% and the rate of resistance according to the species was 2.8% for C.albicans and 11% for non-albicans isolates. No resistance was observed to AMB. Initial treatment was FCZ for 78% and AMB for 22% of the newborns. The treatment was switched to AMB in 15 (28%) cases because of no clinical or laboratory response to FCZ although only three of these babies showed resistance to FCZ (MIC >= 64 mcg/ml). Among the cases with no clinical/microbiological response, C.albicans was the most frequently (66%) isolated species followed by non-albicans species (33%). All of the isolates in the study group were susceptible to AMB and the rate of FCZ resistance was 5.5%. However, it was noted that the clinical treatment failure was higher than the resistance rate when FCZ was considered. Although antifungal susceptibility tests are helpful for guiding the therapy, in vivo and in vitro differences should be taken into account in case of treatment failure encountered with the use of in vitro effective agents.
Keywords: Candida; candidiasis; antifungal susceptibility; fluconazole; amphotericin B; newborn; BLOOD-STREAM INFECTIONS; INTENSIVE-CARE; FLUCONAZOLE PROPHYLAXIS; SURVEILLANCE; RESISTANCE; ALBICANS; INFANTS; COLONIZATION; EPIDEMIOLOGY; MANAGEMENT